Good office design - Littlefield, David (RIBA Publishing, 2009)
This book examines the trends and innovations at the cutting edge of office design in the UK today. Selected from British Council for Offices Award winners since 2002 and interpreting empirical analyses by Davis Langdon, the varied and stunningly illustrated case studies presented here demonstrate the latest thinking from the world of workplace design. Taken together, they offer insight and inspiration for architects, developers, clients and anyone interested in getting the very best out of places of work. The text is sharp and authoritative, and complemented by colour photographs, floor plans, elevations and detail drawings. The chapters are organised into salient topics the Workplace, Location, Structure, Cost and Sustainability but along the way take account of numerous critical issues such as light levels and staff amenities. A wide-ranging end chapter, written by Jeremy Myerson and Paul Warner, knits together contemporary socio-cultural influences to imagine the future of the office.